Impact of intermittent renewable energy production on specific CO2 and NOx emissions from large scale gas-fired combined cycles. (1st June 2019) - Blondeau, J.; Mertens, J.
Abstract: The growing share of intermittent renewable energy sources in electricity production allows for a significant reduction of the emissions of CO2 and other pollutants from conventional, thermal power plants. As a side effect, it also leads to a noticeable increase of the number of start-ups and fast load transients encountered by those power plants used as back-up units. During such transient phases, the performances of those units in terms of pollutant emissions and thermal efficiency are however degraded, which results in a possible reduction of the environmental benefits of renewables that was not yet quantified. In this study, ten years of process data from a representative, large scale gas-fired combined cycle plant that underwent such a transition are analysed to assess the impact of frequent start-ups and load cycling on its average specific CO2 and NO x emissions (per produced MWh e ). While start-up and fast transient phases historically contributed to less than 5 % of the produced power, this share now reaches 5 − 20 % . As a consequence of the increased occurrence of such transients, the average specific NO x emissions increase by 30 to 80 %, from 140 up to 250 g/MWh e, and the average specific CO2 emissions, less impacted, increase by 2 to 4 %, from 335 kg/MWh e up to 350 kg/MWh e . The impact of these findings on the expected reduction of CO2 and NO x emissions attributable to the deployment of renewables is assessed. NO x emissions reduction is significantly lower than expected, due to the increased transient operation of conventional units. For shares of renewable sources lower than 30 %, the additional NO x emissions caused by peak demand operation of the thermal units compensate the emissions saved by decreasing their number of operating hours, resulting in a status quo in terms of global NO x emissions for the most optimistic scenario in terms of LCA emissions from renewable sources. For other scenarios, the global NO x emissions even increase for shares of renewables lower than 30 %, up to 110 % of the initial value (no renewables). As CO2 emissions are much less sensitive to transient phases, the expected CO2 emissions reduction is marginally affected by peak demand operation. Means of reducing both the occurrence of transient phases (at the level of the grid), and the related NO x emission peaks (at the level of the power plants) should be investigated, for a better integration of renewable sources and existing thermal assets. Highlights: The growth of renewables increases the number of transient phases in CCGT plants. Their impact on specific CO2 and NOx emissions was quantified on real data. CO2 emission reduction due to growth of renewables is only marginally affected. The NOx emission reduction is significantly lower than expected due to transience. The renewables share needs to exceed at least 30% for overall NOx reduction.